2020
DOI: 10.1016/j.thromres.2020.04.026
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer as a stand-alone test to rule out deep vein thrombosis

Abstract: Background: Current guidelines recommend the use of clinical decision rules, such as Wells score, in combination with D-dimer to assess the need for objective imaging to rule out deep vein thrombosis (DVT). However, the clinical decision rule has limitations, and use of D-dimer as a stand-alone test has been suggested. Objective:We aimed to assess the safety and efficiency of D-dimer as a stand-alone test to rule out DVT in outpatients referred with suspected DVT. Methods:We collected data from consecutive out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…Plasma D-dimer is a specific marker of hypercoagulation and secondary fibrinolytic activity, therefore, it is widely used for excluding VTE with the threshold as 500 ng/ml since its high prognostic sensitivity [29]. Since plasma D-dimer level increases with age, tumor, surgery, infection and some other disease status, age-adjusted D-dimer cutoff levels were reported to help to rule out PE among cancer patients [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma D-dimer is a specific marker of hypercoagulation and secondary fibrinolytic activity, therefore, it is widely used for excluding VTE with the threshold as 500 ng/ml since its high prognostic sensitivity [29]. Since plasma D-dimer level increases with age, tumor, surgery, infection and some other disease status, age-adjusted D-dimer cutoff levels were reported to help to rule out PE among cancer patients [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer is a degradation product of cross-linked fibrin, which reflects the fibrinolysis status of the system. D-dimer level screening is an exclusion test, with the reason that elevated D-dimer level can be seen in various diseases, including DVT as well [11].…”
Section: Introductionmentioning
confidence: 99%
“…DD is a fibrin-specific degradation product produced by plasmin hydrolysis. An increase in the level of D-dimer indicates that the body is in a hypercoagulable state, which promotes the formation of BMP [ 22 ]. Relevant studies have found that DD is significantly increased in CAP patients requiring hospitalization, and it is related to disease severity and survival rate [ 23 ].…”
Section: Discussionmentioning
confidence: 99%